2022
DOI: 10.1177/10225536221095969
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction with lateral extra-articular tenodesis reduces knee rotation laxity and graft failure rate: A systematic review and meta-analysis

Abstract: Purpose To determine whether the addition of lateral extra-articular tenodesis (LET) to anterior cruciate ligament reconstruction (ACLR) reduces rotational laxity of the knee, and to compare the clinical results of this treatment with those of ACLR alone. Methods PubMed, Embase, and Cochrane Library were searched by two researchers for clinical studies comparing ACLR with and without LET. Studies with only evidence levels I and II and studies in which anterior lateral ligament reconstruction was performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
1
8
0
1
Order By: Relevance
“…However, a pilot study by Di Benedetto et al 30 on 16 patients aged 21 to 37 years who underwent ACLR + LET revealed reacquisition of sagittal knee stability and gait dynamics to the preoperative level. These findings are also supported by a meta-analysis by Feng et al, 31 who reported that, in 1,745 patients, ACLR + LET provided reduced pivot-shif,t with an odds ratio of 0.48 (95% CI: 0.31 to 0.74), and better graft failure rate, with an odds ratio of 0.34 (95%CI: 0.20 to 0.55).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, a pilot study by Di Benedetto et al 30 on 16 patients aged 21 to 37 years who underwent ACLR + LET revealed reacquisition of sagittal knee stability and gait dynamics to the preoperative level. These findings are also supported by a meta-analysis by Feng et al, 31 who reported that, in 1,745 patients, ACLR + LET provided reduced pivot-shif,t with an odds ratio of 0.48 (95% CI: 0.31 to 0.74), and better graft failure rate, with an odds ratio of 0.34 (95%CI: 0.20 to 0.55).…”
Section: Discussionsupporting
confidence: 66%
“…No entanto, um estudo piloto realizado por Di Benedetto et al 30 em 16 pacientes com idades entre 21 e 37 anos submetidos à RLCA + TEL revelou a reaquisição da estabilidade sagital do joelho e da dinâmica da marcha no nível anterior ao da cirurgia. Esses achados também são apoiados por uma metanálise realizada por Feng et al, 31 que relataram que, em 1.745 pacientes, a RLCA + TEL proporcionou redução do mudança do pivô, com uma razão de chances de 0,48 (IC95%: 0,31 a 0,74) e melhor taxa de falha do enxerto, com uma razão de chances de 0,34 (IC95%: 0,20 a 0,55).…”
Section: Discussionunclassified
“…Joint degeneration, % ( Recent literature showed that additional anterolateral augmentation procedures help to reduce graft failure rates in young patients, who have the highest risk for graft failure [15,13].…”
Section: Complicationsmentioning
confidence: 99%
“…High‐risk patients may benefit from anterolateral augmentation procedures during ACL reconstruction (ACLR) [ 45 ]. Anterolateral augmentation procedures have recently generated increased focus regarding their ability to augment an ACLR to reduce graft failure rates [ 4 , 13 , 15 , 33 , 39 ]. These procedures can be divided into lateral extra‐articular tenodesis (LET) and anterolateral ligament reconstruction (ALLR) techniques [ 33 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Great emphasis has been given to a better understanding of these structures, including their anatomy, biomechanics, injury patterns, and the optimal strategies to treat any rotational laxity of the knee resulting from damage to these structures[ 6 ]. Lateral extra-articular tenodesis has re-emerged in popularity and several ALL reconstruction techniques have been developed in the attempt to lower the failure rate following ACL reconstruction[ 7 - 9 ]. The aim of this review is to outline the latest literature findings on the anatomy of the anterolateral complex, biomechanical findings, treatment of anterolateral lesions, and ALL reconstruction techniques.…”
Section: Introductionmentioning
confidence: 99%